UNIVERSAL DESIGN FOR LEARNING AND ASSISTIVE TECHNOLOGY: COMPLEMENTARY OR EXCLUDING? - Paiva e Oliveira, Amalia Reboucas de; Goncalves, Adriana Garcia; Presumido Bracciali, Ligia Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2021)
With the advances in researches and legislation about educational inclusion a lot of theories and actions have emerged in order to support the inclusion of students with disabillitis in the school context, among them we highlight the Uniserval Ddesign for Learning (DUA) and the use of Assistive Technology (AT). This article presentes a theoretical discussion based on the principles of Universal Design for Learning and Assistive Technology, to this end we discuss how the literature has pointed out that these perspectives, although they seem incompatible at first sight, they can favor and be complementary in the process of educational inclusion.
Keywords: Universal design for learning; Assistive tecnology; School inclusion